In vitro Plant Regeneration from Axillary Buds of Asparagus racemosus Wild, a Medicinal Plant - Afroz, F; Jahan, MAA; Hassan, AKM Sayeed; Khatun, R (Bangladesh Journal of Scientific and Industrial Research, 2010)
An efficient method was developed for regeneration of Asparagus racemosus Wild, from axillary explants. MS media supplemented with different concentrations of cytokinin (BAP) alone or in combination of different concentrations of auxin (NAA or IBA) was tested for their efficiency in multiple shoot induction. High frequency of multiple shoot regeneration was achieved on MS medium supplemented with BAP (0.1mg/l) and NAA (0.05 mg/l). When shoots were well developed they were dissected and subcultured on the same medium to promote more multiple shoots. Eighteen to twenty shoots were obtained on this medium. The shoots were rooted best on half MS medium supplemented with 0.05 mg/l BAP and 1.0 mg/l IBA. Among the five levels of pH tested, 5.7 was the best for multiple shoot proliferation. The result presented here proved to be suitable for the rapid propagation system of A. racemosus. Key words: Asparagus racemosus; Medicinal plant; Rapid proliferation; Multiple shoots; Auxins and Cytokinins DOI: 10.3329/bjsir.v45i3.6534 Bangladesh J. Sci. Ind. Res. 45(3), 255-260, 2010